2017
DOI: 10.1016/j.bbrep.2017.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Crocin, a plant-derived carotenoid, modulates microglial reactivity

Abstract: Microglia activation plays an important role in immune responses in the CNS including the retina. Crocin, a plant-derived carotenoid, has been reported to possess anti-inflammatory, anti-apoptotic and anti-oxidative capacity in models of retinal damage and degeneration. If these neuroprotective effects could be mediated by direct modulation of microglial cells is unclear. Here, we examined the direct effects of crocin on key functions and pro-inflammatory gene expression in lipopolysaccharide (LPS)-activated B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…BB extract in combined treatment with LPS was able to partially reverse this phenotype. This data are consistent with the study of Yorgun et al (2017), showing that crocin treatment, a plant-derived carotenoid, reverses LPS ameboid phenotype in BV-2 microglial cells [ 63 ]. In addition, resveratrol, one the main polyphenols of grape, induces filopodia formation in a time- and concentration-dependent manner in MDA-MB-231 human breast cancer cells [ 64 ].…”
Section: Discussionsupporting
confidence: 93%
“…BB extract in combined treatment with LPS was able to partially reverse this phenotype. This data are consistent with the study of Yorgun et al (2017), showing that crocin treatment, a plant-derived carotenoid, reverses LPS ameboid phenotype in BV-2 microglial cells [ 63 ]. In addition, resveratrol, one the main polyphenols of grape, induces filopodia formation in a time- and concentration-dependent manner in MDA-MB-231 human breast cancer cells [ 64 ].…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, amyloid- β accumulates in drusen in the eyes of patients with AMD, and crocin has been shown to reduce NO release from microglia stimulated with interferon- γ and amyloid- β [ 85 ]. In a similar study, crocins stimulated microglial phagocytosis, which is important for retinal homeostasis, and significantly reduced gene expression of IL-6 and CCL2 [ 86 ]. These authors also reported that crocin inhibited iNOS gene expression and NO production in LPS-challenged BV-2 microglia [ 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a similar study, crocins stimulated microglial phagocytosis, which is important for retinal homeostasis, and significantly reduced gene expression of IL-6 and CCL2 [ 86 ]. These authors also reported that crocin inhibited iNOS gene expression and NO production in LPS-challenged BV-2 microglia [ 86 ]. These results suggest that crocins and crocetin may provide neuroprotection by reducing the production of various neurotoxic molecules by activated microglia.…”
Section: Resultsmentioning
confidence: 99%
“…Geniposide also showed similar protective effects in LPS-exposed macrophages and in mice challenged with LPS ( 42 ). Crocin, another active compound identified in G. Jasminoides , also showed anti-inflammatory activity by decreasing the expression of proinflammatory cytokines and decreasing nitric oxide production ( 43 , 44 ).…”
Section: Discussionmentioning
confidence: 99%